Country‐ and individual‐level determinants of probable problematic gambling in adolescence: a multi‐level cross‐national comparison. (December 2014) - Molinaro, Sabrina; Canale, Natale; Vieno, Alessio; Lenzi, Michela; Siciliano, Valeria; Gori, Mercedes; Santinello, Massimo
Abstract Aims To estimate the role of family and socio‐economic indicators of welfare state in accounting for probable problem gambling during adolescence in a representative sample of students living in nine European countries. Design Data from the 2011 European School Survey Project on Alcohol and Other Drugs (ESPAD) Study were used for cross‐sectional analyses of adolescent probable problem gambling. Setting Representative surveys in nine European countries. Participants A total of 31 236 16‐year‐old students. Measurements Respondents' probable problem gambling, socio‐demographic characteristics and parenting (regulation, monitoring and caring) were measured individually. Indicators of wealth (gross domestic product per capita, GDP), expenditure on public health (% GDP) and benefit in kind for families/children (% GDP) were obtained from national public databases. Findings Students who perceived more parental caring [odds ratio (OR) = 0.92, 95% confidence interval (CI) = 0.85–0.98] and monitoring (OR = 0.57, 95% CI = 0.53–0.62) reported less involvement in probable problem gambling. Moreover, students who perceived stronger parental regulation (OR = 1.16, 95% CI = 1.09–1.23) were more likely to be possible problematic gamblers. At the country level, expenditure on public health was associated negatively with probable problem gambling (OR = 0.87, 95% CI = 0.78–0.97), whereas GDP per capita (OR = 1, 95% CI = 1.00–1.00) and the benefits in kind for families/children (OR = 1.16, 95% CI = 0.89–1.51) showed no association with probable problem gambling. Conclusions Family characteristics and expenditure on public health may play a key role in explaining probable problem gambling among adolescents in Europe.